ICL (Encyclopedia of Ophthalmology, 2018)
Zanubrutinib, a second-generation Bruton tyrosine kinase inhibitor used in B-cell malignancies, has a favorable systemic safety profile, whereas its ocular surface effects remain insufficiently defined. We report a 73-year-old woman receiving zanubrutinib for mantle cell lymphoma who presented with acute pain and decreased vision in the right eye. Slitlamp examination revealed a corneal epithelial defect with an associated stromal infiltrate in the right eye and bilateral epithelial surface abnormalities. The patient reported three months of bilateral ocular irritation and conjunctival hyperemia before this acute presentation. Corneal cultures grew Moraxella nonliquefaciens. Topical antimicrobial therapy resulted in resolution of the infiltrate. However, ongoing bilateral epithelial instability with microcystic changes required adjunctive topical corticosteroids, leading to substantial clinical improvement. The prolonged bilateral prodrome preceding the acute infectious episode, together with the absence of prior ocular disease, raises concern for zanubrutinib-associated ocular surface dysfunction predisposing to secondary infection. To the best of our knowledge, this is the first report suggesting an association between zanubrutinib therapy and corneal surface disease. This case raises a potential ocular side effect of zanubrutinib, emphasizing the need for further investigation. As immunotherapy use expands, ophthalmologists should remain vigilant for emerging ocular toxicities and collaborate with oncology specialists for optimal patient care.